America's global advantage : US hegemony and international cooperation - Norrlof, Carla (Cambridge ; Cambridge University Press, 2010)
'For over 60 years the U.S. has been the largest economy and most powerful country in the world. However, there is growing speculation that this era of hegemony is under threat as it faces huge trade deficits, a weaker currency, and stretched military resources. America's Global Advantage argues that, despite these difficulties, the U.S. will maintain its privileged position. In this original and important contribution to a central subject in International Relations, Carla Norrlof challenges the prevailing wisdom that other states benefit more from U.S. hegemony than the United States itself. By analysing America's structural advantages in trade, money, and security, and the ways in which these advantages reinforce one another, Norrlof shows how and why America benefits from being the dominant power in the world. Contrary to predictions of American decline, she argues that American hegemony will endure for the foreseeable future'--Provided by publisher.
Introduction -- The forms and consequences of hegemonic leadership -- Cooperation under hegemony -- International trade cooperation -- Interactive effects between monetary and commercial power --The security card -- Credible threats and regional competition.
Includes bibliographical references and index.
Keywords: Hegemony -- United States; International cooperation; International relations